Evaluación de riesgos ergonómicos y desarrollo de un manual preventivo en la microempresa enderezada y pintura automotriz Wilson de la ciudad de Riobamba - Guapi Tixi, Cristhian Jhonatan (2025)
In the microenterprise "Enderezado y Pintura Automotriz Wilson," a series of ergonomic risks impacting the health of its workers were identified. The main issues are associated with the adoption of forced postures, handling heavy loads, and exposure to chemicals. These conditions have led to a high incidence of musculoskeletal problems, skin and eye irritation, as well as generalized fatigue among employees. As a result, the main objective was set to evaluate these risks in the microenterprise, with the aim of developing a prevention manual to mitigate occupational injuries and improve working conditions. To carry out this evaluation, a quantitative approach was adopted, which allowed for the identification of the movements and postures that workers perform on a daily basis. Ergonomic methods such as RULA, OWAS, and NIOSH were used. The research was conducted under a non-experimental design, involving a population of 8 workers. The results revealed that most employees, especially those in the positions of automotive painter, bodywork straightener, and detailing specialist, face moderate to high ergonomic risk levels. These positions require immediate interventions to reduce the impact on workers' health and improve the overall productivity of the company.